Effect of xanthan gum‐thickened liquid aspiration on the lungs in a mouse model. Issue 2 (21st January 2020) - Araie, Takafumi; Ono Minagi, Hitomi; Usami, Yu; Ikai, Kazuki; Sakai, Manabu; Gojo, Nao; Nohara, Kanji; Sakai, Takayoshi
Abstract: Objectives/Hypothesis: To modify liquid viscosity is a common practice used in patients with dysphagia to avoid aspiration. Although accidentally aspirating small amount occurs frequently in patient‐care settings, the effect of aspirating a small amount thickened fluids on lungs is not clear. The purpose of the present study was to investigate the effect of xanthan gum‐thickened liquid aspiration on the lungs. Methods: ICR mice were randomly divided into three experimental groups: saline, low thickened saline, and high thickened saline. To induce aspiration, we administered each reagent through a single intratracheal instillation at a dose of 0.3 ml kg −1 body weight. The mice were euthanized at specific time points (at 1, 3, and 7 days), and the respiratory clearance of the aspirated materials and the effects of the aspiration on lung tissue, physiological function, inflammatory responses, and alveolar capillary barrier permeability were evaluated. Results: The results showed that when thickened saline was aspirated, the aspirated material did not spontaneously resolve for at least a week in the lungs, though saline did. In addition, thickened saline aspiration caused short‐term inflammatory responses and a prolonged increase in alveolar capillary barrier permeability. The alterations of the alveolar capillary barrier permeability remained significantly elevated at day 7 in high thickened saline compared with saline. There were no significant differences in the physiological and histological findings between the aspiration of saline and thickened saline. Conclusions: These results suggest that xanthan gum‐thickened liquid aspiration can extend the duration of lung injury.